Can Radiation Dose Be Reduced and Image Quality Improved With 80-kV and Dual-Phase Scanning of the Lower Extremities With 64-Slice Computed Tomography Angiography?. Issue 5 (September 2015) - Zhou, Yunfeng; Wang, Juan; Dassarath, Meera; Wang, Minhong; Zhang, Qiang; Xiong, Yuwei; Yuan, Quan
<x xml:space="preserve">Abstract</x> Objective To prospectively compare the new computed tomographic angiography (CTA) protocol (NCP) using 80-kV and dual-phase scanning with the routine CTA protocol (RCP) using 120-kV and single-phase scanning in patients with peripheral arterial disease. Methods A total of 60 patients were randomized to undergo the NCP (30 patients) or RCP (30 patients) scan. We compared the arterial attenuation values, overriding of the contrast bolus, signal-to-noise ratio, and radiation dose between 2 groups. Results The occurrence rate of contrast bolus overriding was not statistically significant (P = 0.69). The average arterial attenuation value in the NCP group was significantly higher (P < 0.05) than that in the RCP group. The radiation dose in the RCP group was significantly higher (P < 0.001) than that in the NCP group. The mean signal-to-noise ratio in the NCP group was significantly lower (P < 0.001). Conclusions Sixty-four-slice CTA with the NCP can significantly reduce the radiation dose and improve the arterial enhancement and calf arteries imaging.